“Candidatus Gortzia shahrazadis”, a Novel Endosymbiont of Paramecium multimicronucleatum and a Revision of the Biogeographical Distribution of Holospora-Like Bacteria - Serra, Valentina; Fokin, Sergei I.; Castelli, Michele; Basuri, Charan K.; Nitla, Venkatamahesh; Verni, Franco; Sandeep, Bhagavatula V.; Kalavati, Chaganti; Petroni, Giulio (Frontiers in Microbiology, 2016)
Holospora spp. and “Candidatus Gortzia infectiva”, known as Holospora-like bacteria (HLB), are commonly found as nuclear endosymbionts of ciliates, especially the Paramecium genus. HLB are related by phylogenetic relationships, morphological features, and life-cycles, which involve two alternating morphotypes: reproductive and infectious forms (RF, IF). In this paper we describe a novel species belonging to the “Ca. Gortzia” genus, detected in P. multimicronucleatum, a ciliate for which infection by an HLB has not been reported, discovered in India. This novel endosymbiont shows unusual and surprising features with respect to other HLB, such as large variations in IF morphology and the occasional ability to reproduce in the host cytoplasm. We propose the name of “Candidatus Gortzia shahrazadis” for this novel HLB. Moreover, we report two additional species of HLB from Indian Paramecium populations: “Ca. Gortzia infectiva” (from P. jenningsi), and H. obtusa (from P. caudatum); the latter is the first record of Holospora from a tropical country. Although tropical, we retrieved H. obtusa at an elevation of 706 m corresponding to a moderate climate not unlike conditions where Holospora are normally found, suggesting the genus Holospora does exist in tropical countries, but restricted to higher elevations.